This Moose Belongs To Me - Oliver Jeffers (Harper Collins Children's Books, 2012)
"Wilfred owned a moose. He hadn't always owned a moose. The moose came to him a while ago and he knew, just KNEW that it was meant to be his. He called it Marcel."Most of the time Marcel is very obedient, abiding by Wilbur's book of extensive rules on how to be a good pet. But sometimes he doesn't quite seem to be listening, plus he has a tendency to wander off wherever he pleases when they go out walking. But Wilfred is still very proud to have a pet like Marcel.Until one day, deep in the woods, someone else seems to recognise Marcel! Is Marcel really Wilfred's pet after all?A lavishly-llustrated, thought-provoking story, which cleverly and light-heartedly examines the concept of ownership.
Keywords: Circle Time -- Circle Time; Relationships / Teamwork /Conflict Resolution -- Relationships / Teamwork /Conflict Resolution